2009
DOI: 10.1074/jbc.m806778200
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of Genes Encoding Anti-microbial Peptides in Drosophila

Abstract: Secretion of antimicrobial peptides (AMPep) is a central defense mechanism used by invertebrates to combat infections. In Drosophila the synthesis of these peptides is a highly regulated process allowing their rapid release in the hemolymph upon contact with pathogens and the arrest of their production after pathogen clearance. We observed that AMPep genes have either a transient or sustained expression profile in S2 Drosophila cells treated with peptidoglycan. Moreover, AMPep genes containing AU-rich elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 38 publications
3
47
1
Order By: Relevance
“…1B). As described previously (23), this degradation phase of the mRNA is concomitant with a further decrease in length of the remaining pool of messenger RNA (Fig. 1A, lanes 4 -8).…”
Section: Overexpression Of Dtis11 Accelerates the Degradation Of Cecamentioning
confidence: 81%
See 4 more Smart Citations
“…1B). As described previously (23), this degradation phase of the mRNA is concomitant with a further decrease in length of the remaining pool of messenger RNA (Fig. 1A, lanes 4 -8).…”
Section: Overexpression Of Dtis11 Accelerates the Degradation Of Cecamentioning
confidence: 81%
“…Recently, we and others have shown that AMD is conserved in Drosophila. In this organism, dTIS11 regulates the stability of ARE-containing mRNAs including messenger RNAs involved in the immune response, such as antimicrobial peptide-coding mRNAs (23)(24)(25). We have observed that AMD requires the CAF1 protein in Drosophila.…”
mentioning
confidence: 83%
See 3 more Smart Citations